Mechanical efficiency and force-time curve variation during repetitive jumping in trained and untrained jumpers - McBride, J. M.; Snyder, J. G. (European Journal of Applied Physiology, 2012)
Mechanical efficiency (ME), the ratio between work performed and energy expenditure, is a useful criterion in determining the roles of stored elastic energy and chemically deduced energy contributing to concentric performance in stretch-shortening cycle movements. Increased force production during the eccentric phase has been shown to relate to optimal muscle-tendon unit (MTU) length change and thus optimization of usage of stored elastic energy. This phenomenon, as previously reported, is reflected by higher jump heights and ME. The purpose of this investigation was to determine if ME may be different between trained and untrained jumpers and thus be accounted for by variation in force production in the eccentric phase as a reflection of usage of stored elastic energy during various jump types. This investigation involved 9 trained (age 20.7 ± 3.2 years, height 178.6 ± 5.3 cm, body mass 79.0 ± 5.5 kg) and 7 untrained (age 21.43 ± 2.37 years, height 176.17 ± 10.89 cm, body mass 78.8 ± 12.5 kg) male jumpers. Trained subjects were Division I track and field athletes who compete in the horizontal or vertical jumping or running events. Force-time and displacement-time curves were obtained during jumping to determine jump height and to calculate work performed and to observe possible differences in force production in the eccentric phase. Respiratory gases with a metabolic cart were obtained during jumping to calculate energy expenditure. ME was calculated as the ratio between work performed and energy expenditure. The subjects completed four sessions involving 20 repetitions of countermovement jumps (CMJ) and drop jumps from 40 cm (DJ40), 60 cm (DJ60) and 80 cm (DJ80). The trained jumpers jumped significantly higher in the CMJ, DJ40, DJ60 and DJ80 conditions than their untrained counterparts (p < 0.05). ME was significantly higher in the trained in comparison to the untrained jumpers during DJ40. The amount of negative work during all jump types was significantly greater in the trained jumpers. There was a significant correlation between negative work and ME in the trained jumpers (r = 0.82) but not in the untrained jumpers (r = 0.54). The present study indicates that trained jumpers jump higher and have greater ME, possibly as a result of increased for production in the eccentric phase as a reflection of optimal MTU length change and thus increased usage of storage of elastic energy.